2020
DOI: 10.1016/j.alter.2020.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The circumstances of migrant families raising children with disabilities in five European countries: Updating knowledge and pursuing new research

Abstract: La situation des familles migrantes ayant un enfant en situation de handicap dans cinq pays européens. Pour le renouvellement des connaissances et le développement de recherches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…As discussed so far, people with disabilities are often victims of negligence and ignorance in society (Presler-Marshall et al, 2020) and experience intersecting vulnerabilities (Lund, 2020;Piérart et al, 2020), as demonstrated by the findings of Cov_enable. The focus laid mainly on the interaction of gender, poverty, and race should not neglect disability as an intersectional category of inequality (Frederick & Shifrer, 2019;Garland-Thomson, 2005;Gerschick & Stevens, 2016).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As discussed so far, people with disabilities are often victims of negligence and ignorance in society (Presler-Marshall et al, 2020) and experience intersecting vulnerabilities (Lund, 2020;Piérart et al, 2020), as demonstrated by the findings of Cov_enable. The focus laid mainly on the interaction of gender, poverty, and race should not neglect disability as an intersectional category of inequality (Frederick & Shifrer, 2019;Garland-Thomson, 2005;Gerschick & Stevens, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…Accessing the required information and remote support through phone or e-mail communication could lead to additional hurdles for immigrants with disabilities who had language difficulties. A lack of language skills or knowledge about the health care system and support services put immigrant communities in a challenging situation and immigrants with disabilities suffered from cultural and linguistic barriers during the pandemic (Geuijen et al, 2021;Piérart et al, 2020).…”
Section: Disability and Pandemicmentioning
confidence: 99%
“…Furthermore, although the native language of some of our participants was not French and some had migrated to receive care for their child in metropolitan France, only parents with sufficient French language skills were interviewed. The specificity of these experiences needs to be explored further because they can affect access to support and the shape of parenting work 47 . It is also important to note that although a large number of emotions could be expressed over the telephone (e.g., crying, sniffing, laughing, hesitations, intonations), facial and gestural expressions were missed.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The specificity of these experiences needs to be explored further because they can affect access to support and the shape of parenting work. 47 It is also important to note that although a large number of emotions could be expressed over the telephone (e.g., crying, sniffing, laughing, hesitations, intonations), facial and gestural expressions were missed. However, when the study began, COVID-19 was not quite over.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Worldwide, the group of migrant children with ID is estimated at 5 million (Bešic & Hochgatterer, 2020). Due to linguistic and cultural differences, lack of knowledge about the healthcare system, and their socio-economic circumstances (Piérart et al, 2020), migrant parents of children with ID have been found to have higher needs for information and financial support (Oner et al, 2020). One of the first studies exploring experiences of migrant parents of children with ID showed that migrant parents described accessing healthcare as challenging, since they felt that their concerns about their child with ID had not been taken seriously and that they did not receive the help they needed (Arfa et al, 2020).…”
mentioning
confidence: 99%